A companion to late ancient Jews and Judaism: third century BCE to seventh century CE - Koltun-Fromm, Naomi; Kessler, Gwynn ca. 21. Jh. (Blackwell companions to the ancient world, 2020)
Introduction / Gwynn Kessler and Naomi Koltun-Fromm -- Where Jews Lived in the West? / Ross Kraemer -- Jewish Towns and Neighborhoods in Roman Palestine and Persian Babylonia / Mika Ahuvia -- Late Ancient Jewish Languages / Azzan Yadin-Israel -- Literature of the Jews, Fourth Century B.C.E. to Second Century C.E. / Eva Mroczek -- Rabbinic Literature / Michal Bar Asher-Siegal -- Material Culture of the Second Temple Period (pre-70 C.E.) / Karen B. Stern -- How Do Jews Matter? Exploring Late-Ancient Mediterranean Jews and Jewishness through Material Culture / Cynthia M. Baker -- Material Culture of the Jews in the Sasanian Empire / Jason S. Mokhtarian -- Non-Jewish Sources for Late Ancient Jewish History / Naomi Koltun-Fromm -- Contesting Identities: The Splitting Channels from Israelite to Jew / Yair Furstenberg -- Imagining Judaism after 70 C.E. / Jonathan Klawans -- Rabbis and the Poor in Palestinian Amoraic Literature and the Babylonian Talmud / Alyssa M. Gray -- Diaspora and Center / Joshua Burns -- Jews and their Others (New Testament) / Sandy L. Haney -- Rabbis and their Others / Mira Beth Wasserman -- What is Jewish Law? -- Jewish Legal Culture and Thought in Antiquity (Fifth C. B.C.E. -- Seventh C. C.E.) / Natalie B. Dohrmann -- Arabian Judaism at the Advent of Islam: A Forgotten Chapter in the History of Judaism / Aaron Hughes -- Sexualities and Il/licit Relationships in Late Ancient Jewish Literatures / Federico Dal Bo -- Embodied Scriptural Practice Among Late Ancient Jews / Elizabeth Shanks-Alexander -- Bodies that Matter: Piety and Sin / Jane L. Kanerak -- Rabbinic Gender: Beyond Male and Female / Gwynn Kessler -- Disability Studies in Jewish Culture in Late Antiquity: Gender, Body and Violence amidst Empire / Julia Watts Belser -- Gender, Sex and Witchcraft in Late Ancient Judaism / Sara Ronis -- Domestic Spaces / Meredith J. C. Warren -- "Do Not Say 'I am Poor and Cannot Seek out Knowledge": The House of Study and Education in the Second Temple Period / Cana Werman -- Locating Diaspora Jewish Philanthropy in the Ancient Mediterranean Public Arena / Shira L. Lander -- Sacred Spaces / Sarit Kattan Gribetz -- Jewish Prayer, Liturgy and Ritual / Laura S. Lieber -- Agriculture and Industry / John Mandsanger.